HARGA DIRI DAN DUKUNGAN SOSIAL KELUARGA TERHADAP OPTIMISME PERENCANAAN KARIR PADA REMAJA PUSAT PENGEMBANGAN ANAK SEMARANG - Purnomo, Ambarwati; Hariadi, Lucy; Permitasari, I Rheny Arum; Argasiam, Brigitan (Psikologi Prima, 2023)
This determined the relationship between self-esteem and family social support on the optimism of adolescent career planning at the Semarang Child Development Center. The hypothesis is that there is a positive relationship between self-esteem and career planning optimism, assuming that the higher the self-esteem of adolescents, the higher the optimism of adolescents in career planning. There is a positive relationship between family social support and career planning optimism, assuming that the higher the family social support, the higher Adolescents are optimistic in planning a career, there is a positive relationship between self-esteem and family social support on career planning optimism, with the assumption that the higher the self-esteem and family social support, the more optimistic adolescents are in determining a career. The research subjects in this study used a saturated sample of adolescents aged 15-18 years at the Semarang Child Development Center. The test carried out in this study is an assumption test that contains a normality test and a relationship linearity test. This study uses Product Moment correlation using SPSS 23 for Windows. The results of the data analysis obtained are the correlation coefficient of 0.659 with a significance of 0.000, r_x1y = 0.659 (p <0.01), meaning that the hypothesis is acceptable, namely that there is a positive relationship between the variable self-esteem and optimism for career planning, the second hypothesis obtained a value of 0.589 with a significance of 0.000 , r_x2y = 0.589 (p <0.01) means that the hypothesis is accepted, namely that there is a positive relationship between the variable family social support on career planning optimism, then the third hypothesis obtained a value of 0.692, an R square value of 0.479, an F value of 68.853 with a significance level of 0.000. A significance of 0.000 is smaller than alpha 0.01, meaning that the hypothesis is accepted indicating a simultaneous relationship between self-esteem and family social support variables on optimism in career planning.